(untitled) (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2023)
The SISKEUDES application is a financial management system application designed by the Ministry of Home Affairs together with the Financial and Development Supervision Agency in accordance with the Ministry of Home Affairs Regulation No. 113 of 2014 regarding the Village Management System. This digital innovation is useful in facilitating the performance of village officials in the village financial reporting process. However, in its use, the SISKEUDES application is still a challenge for the officials of Karang Mukti Village, where Karang Mukti Village is included as a Digital Village pilot. The purpose of this study is to describe the implementation of the use of the SISKEUDES application in Karang Mukti Village. In analyzing, researchers use the theory of Policy Implementation from Charles O. Jones to be able to explain in more detail related to this problem. This research uses qualitative methods of case studies, as well as in-depth interviews with key informants; the Village Head; Head of Village Planning; and Head of Village Finance. The results of this study show that (1) a lack of readiness of human resources in organizations in Karang Mukti Village; (2) Direction given by the central and local governments is lacking; (3) The implementation of the SISKEUDES application in Karang Mukti Village is still often constrained both technically and because the village network is quite difficult. Thus, the implementation of the SISKEUDES application still cannot be said to have been effective. This research is expected to be taken into consideration for the re-evaluation of policymakers in addressing the implementation of digital-based financial management in each village.